Adverse Childhood Experiences and Health-Risk Behaviors in Vulnerable Early Adolescents - Garrido, Edward F. (J Early Adolesc, 2017)
Adverse childhood experiences (ACEs) are associated with health-risk behaviors in general samples of adults and adolescents. The current study examined the association between ACEs and these behaviors among a high-risk sample of early adolescents. Five hundred and fifteen 9-11-year-old children placed in foster care due to maltreatment were interviewed about their engagement in violence, substance use, and delinquency. A multi-informant ACEs score was derived based on exposure to six adverse experiences. Regression analyses examined the relationship between ACEs and risk behaviors and the potential moderating effects of age, sex, and minority status. ACE scores were predictive of risk behaviors after controlling for age, sex, and minority status. Although males and older youth were more likely to engage in risk behaviors, none of the demographic characteristics moderated the ACE-risk behavior association. This study extends previous research by demonstrating an association between ACEs and risk behaviors in extremely vulnerable early adolescents.